Management of Artesian Wells at Bumi Purnawira Housing Sukabumi City with Water Distribution Application - Jatmika, Bambang; Paikun, Paikun; Resdiawan, Wisnu (Universitas Ibn Khaldun Bogor, 2023)
The problem of clean water supply to meet the needs of the community is the main obstacle experienced by residents of Bumi Purnawira housing. Water management is completely left to the residents starting from installation of pipes to each house, installation of water meters, calculation of the cost of water usage per cubic meter, as well as administration and maintenance of the artesian well. Some problem that arise include: frequent miscalculation of cost to be paid; monthly meter recapitulation records in the form of paper prone to damage and data lost; meter recapitulation records is only kept by the treasurer, so if the residents want to know the history of meter records and the payment, they have to see the treasurer; the meter's monthly status is vulnerable to manipulation whether done by the residents or the treasurer; There is often a discrepancy between the financial recapitulation recorded and the physical cash; and financial expenditures are sometimes not properly recorded, so that it triggers the discrepancy between the recorded amount and the physical cash. Seeing the existing reality, an idea to make an application for the management of artesian well administration has arisen. The initial step is to form two teams, namely the development team and the socialization team. The development team is responsible for developing the management system of the artesian well's administration and finance. Meanwhile, the socialization team is responsible for conducting the socialization and the application training. The result of this project is an application and socialization that can help both the administrators and the residents in managing the administration and finance of the artesian well.